Energizing Sustainability: Solar Cell Radio Wave AI Transformations in Business and Health, with a Focus on Vaccines and Antibiotics - Chen jin Kim (Information Technology and Science (ITScience), 2023)
This review article provides a comprehensive examination of the synergistic integration of several technologies, including radio waves, solar cell technology, artificial intelligence (AI), business information technology (IT), immunizations, and antibiotics, with the aim of fostering sustainable innovation. A comprehensive analysis is carried out, highlighting the connections between smart technology, healthcare, and renewable energy sources. The abstract looks at how solar energy and radio waves might advance technology, with artificial intelligence and business IT aiming to maximize productivity. The evaluation also explores the potentially innovative ways in which vaccinations and antibiotics could enhance public health. By linking different disciplines together, the article aims to shed light on the holistic and long-term strategy that emerges when many technologies come together for the good of business and society. This paper explores the intricate connections between solar cell technology and artificial intelligence (AI), showing how advances formerly unimaginable are propelled by the convergence of advanced computing power and renewable energy sources. When it comes to facilitating the seamless integration of many technologies to optimize productivity and decision-making processes, business IT plays a critical role. The important sector of medicine, where immunizations and antibiotics are critical for creating resilient populations, is also covered in the article. This study explains the potential for comprehensive and long-lasting solutions by combining these technological and medical advancements, while also emphasizing the necessity of multidisciplinary cooperation in tackling the challenges of our rapidly changing environment.